2019
DOI: 10.1016/s1569-9056(19)31011-5
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer prognosis after initiation of androgen deprivation therapy among statin users. A population-based cohort study

Abstract: Purpose Statins' cholesterol-lowering efficacy is well-known. Recent epidemiological studies have found that inhibition of cholesterol synthesis may have beneficial effects on prostate cancer (PCa) patients, especially patients treated with androgen deprivation therapy (ADT). We evaluated statins' effect on prostate cancer prognosis among patients treated with ADT. Materials and methods Our study population consisted of 8253 PCa patients detected among the study population of the Finnish randomized study of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…erefore its application is expected to extend survival after ADT. A recent report shows statins, known to decrease systemic cholesterol levels, significantly improve the benefits of ADT in patients [189]. ese agents reduced the availability of circulating cholesterol for ingestion by TAMs and its transfer towards neighboring tumor cells during ADT, possibly delaying the onset of CRPC.…”
Section: Inhibiting the Crosstalk Between Tams And Tumor Cellsmentioning
confidence: 99%
“…erefore its application is expected to extend survival after ADT. A recent report shows statins, known to decrease systemic cholesterol levels, significantly improve the benefits of ADT in patients [189]. ese agents reduced the availability of circulating cholesterol for ingestion by TAMs and its transfer towards neighboring tumor cells during ADT, possibly delaying the onset of CRPC.…”
Section: Inhibiting the Crosstalk Between Tams And Tumor Cellsmentioning
confidence: 99%
“…However, tumour progression inevitably occurs in spite of low availability of circulating androgens through a variety of documented mechanisms including intratumoral androgen synthesis from cholesterol [56]. As such, it has been hypothesised that statins may synergise with ADT by blocking accumulation of intratumoral cholesterol thereby reducing the substrate for de novo androgen synthesis within the prostate [57]. Given that more advanced tumours upregulate enzymes necessary for de novo androgen synthesis [58][59][60], it may be that statins have a stronger effect in later-stage tumours, enriched in the context of salvage ADT.…”
Section: Current Treatment Landscape: Statins and Androgen Deprivatio...mentioning
confidence: 99%
“…Indeed, inverse associations reported by the various observational studies completed to date (Table 1) appear slightly stronger among patients receiving salvage ADT, typically administrated later during the disease course compared to primary ADT. Among studies where the majority were using salvage ADT, estimates for statin use in association with prostate cancer-specific mortality ranged from HR 0.65 (95% CI 0.48-0.97) [61] to HR 0.86 (95% CI 0.69-1.07) [11], whereas among studies in the context of majority primary ADT, estimates ranged from HR 0.82 (95% CI 0.69-0.96) [57] to HR 0.98 (95% CI 0.72-1.32) [62]. These estimates could support a biological mechanism or be the result of greater difficulty with controlling time-varying confounding in settings of salvage ADT, where data on patient and tumour characteristics are typically known only at diagnosis.…”
Section: Current Treatment Landscape: Statins and Androgen Deprivatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies were published between 2010 and 2021, with at least 6 score of NOS results. Among these studies, 7 studies were conducted in the USA [20,23,24,28,37,41,42], 4 in Canada [21,22,29,40], 4 in China [25,26,31,36], 4 in Finland [19,27,32,34], 1 in Italy [30], 1 in Denmark [33], 1 in Germany [35], 1 in the UK [38], and 1 in Norway [39]. 18 studies reported the association between statin use and PCMS, whereas 17 studies examined ACM.…”
Section: Study Characteristicsmentioning
confidence: 99%